Baseline troponin-T is powerful predictor of mortality after coronary bifurcation stenting. (14th October 2021) - Vassilev, D; Mileva, N; Collet, C; Sokolova, K; Nikolov, P; Karamfiloff, K; Rigatelli, G; Gil, R
Abstract: Introduction: Considerable progress has been made in the treatment of coronary bifurcation stenosis. Anatomical characteristics of the lesion, however, fail to give information about the functional significance of the bifurcation stenosis. There is no study that systematically establishes the baseline functional significance of coronary stenosis and its effect on procedural and clinical outcomes. Methods: Patients with significant angiographically bifurcation lesions defined as diameter stenosis >50% in main vessel and/or side branch were included. FFR was performed in main vessel (MV) and side branch (SB) before and after percutaneous coronary intervention (PCI). If FFR was ≤0.80 the lesion was considered functionally significant, and patients underwent PCI. For the group with FFR >0.80 – intervention was deferred. All patients were followed-up for vital status every 3 months. Cox regression analysis was performed to identify independent predictors of all-cause and cardiovascular death. The local ethics committee approved the study and patients signed informed consent for participation into registry. Results: For mean follow-up of 38±18 months (median 40, IQR 23–55 months) all-cause mortality was numerically lower: 8.5% (n=7/82) in deferred group and 12.6% in stented group (n=11/76, p=0.387). The cardiac mortality was also numerically lower, but statistically not significant (9.8%, n=8/82 vs. 11.5%, n=10/88, p=0.714). On multivariate model, independent predictors were mitral regurgitation >1st degree – HR=1.778 (CI 1.100–2.874, p=0.019); dyslipidemia HR=0.765 (CI 0.594–0.985, p=0.038); hemoglobin concentration – HR=0.976 (CI 0.964–0.988, p<0.001); pre-PCI serum troponin ≥0.010 ng/ml – HR=2.702 (CI 1.451–5.032, p=0.002). On multivariate analysis, the following factors were identified as independent predictors of cardiac mortality: age – HR=1.035 (CI 1.009–1.062, p=0.009); diabetes – HR=1.789 (CI 1.089–2.962, p=0.024); dyslipidemia treated with statin – HR=0.667 (CI 0.515–0.863, p=0.002); LV posterior wall thickness – HR=1.230 (CI 1.062–1.424, p=0.006); mitral regurgitation more than 1st degree – HR=1.763 (CI 1.065–2.917, p=0.027); troponin pre-PCI ≥0.010 ng/ml – HR=2.498 (CI 1.228–5.081, p=0.011); true bifurcation lesion – HR=1.820 (CI 1.026–3.229, p=0.040); SBBARI score <10% – HR=1.715 (CI 1.049–2.804, p-0.031). Conclusion: Baseline high-sensitive troponin T value is a strong predictor for both all cause and cardiac mortality in patients undergoing coronary bifurcation lesion PCI. FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Alexandrovska University Hospital